Scanning electron microscopy of male terminalia and its application to species recognition and phylogenetic reconstruction in the Drosophila saltans group. - Tiago Alves Jorge Souza; Fernando Barbosa Noll; Hermione Elly Melara de Campos Bicudo; Lilian Madi-Ravazzi (PLoS ONE)
The Drosophila saltans group consists of five subgroups and 21 species, most of which have been identified only by morphological aspects of the male terminalia revealed by drawings using a camera lucida and a bright-field microscope. However, several species in the group, mainly those included in the saltans subgroup, are difficult to differentiate using only these characteristics. In this study, we used scanning electron microscopy (SEM) to analyze 19 structures of the male terminalia in 10 species from the five saltans subgroups. Among these structures, nine could be identified only through SEM analysis. We aimed to find other characteristics useful for morphological recognition of these species and to use these characteristics for phylogenetic reconstruction. These morphological differences enabled us to effectively distinguish among sibling species. These findings confirmed the monophyly of this group as previously determined in evolutionary studies based on other markers. The single most parsimonious tree (CI = 87 and RI = 90) indicated that the cordata subgroup is the most basal lineage and the saltans subgroup is the most apical lineage, as shown in earlier studies based on morphological data. However, our findings differed somewhat from these studies with respect to the phylogenetic relationships of species in the saltans group indicating that this group is still a puzzle that remains to be deciphered.